"It doesn’t take much force" : the negotiation of gender by two women motor mechanic apprentices through the biographical lens - Brockmann, Michaela [Verfasser] (My University, 2021)
"The marked and persistent gender segregation in apprenticeship has been well documented. The social construction of ‘male’ and ‘female’ jobs is a key factor in the gendered patterns evident in career choice. Research on young women who have chosen careers in male-dominated occupations risks constructing them as ‘Other’, typically concluding that rather than challenging the gender binary, the women would reinforce it, echoing ‘tomboy’ identities according to which girls are aligning themselves with boys whilst devaluing femininity. Based on biographical interviews, this paper explores the role of gender in the career decision-making of one German and one English woman motor mechanic apprentice. It illustrates the strongly normative but highly contextual nature of gender as the two women negotiate identities in their quests to live ‘liveable lives’. It will be argued that the rich and multi-faceted experiences of these two young women belie stereotypical accounts of gender, suggesting acceptable ways of being in male workspaces." (Author's abstract ; BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; G 2.4.5 Gender Mainstreaming; S 6.2.3 Metallerzeugung und -bearbeitung, Maschinenbau, Montierberufe (inkl. fahrzeugtechnischer Berufe); 370; Berufsbildung; Berufswahl; Gender Mainstreaming; Kraftfahrzeugmechaniker; Frauenberuf; Männerberuf